Ablation of p120-Catenin Altering the Activity of Small GTPase in Human Lung Cancer Cells - Nan LIU; Yang LIU; Shuli LIU; Enhua WANG (Chinese Journal of Lung Cancer, 2009)
Background and objective p120-catenin (p120ctn), a member of the Armadillo gene family, has emerged as an important modulator of small GTPase activities. Therefore, it plays novel roles in tumor malignant phenotype, such as invasion and metastasis, whose mechanism are not well clarified yet. The aim of this study is to explore the roles of p120ctn on the regulation of small GTP family members in lung cancer and the effects to lung cancer invasions andmetastasis. Methods After p120ctn was knocked down by siRNA, in vivo and in vitro analysis was applied to investigate the role and possible mechanism of p120ctn in lung cancer, such as Western Blot, pull-down analysis, and nude mice models. Results p120ctn depletion inactivated RhoA, with the the activity of Cdc42 and Rac1 increased, the invasiveness of lung cancer cells was promoted both in vitro and in vivo . Conclusion p120ctn gene knockdown enhances the metastasis of lung cancer cells, probably by altering expression of small GTPase, such as inactivation of RhoA and activation of Cdc42/Rac1.